Accelerated carcinogenesis of colorectal cancer - Lam, XiuQian (2021)
Background: Colorectal cancer (CRC) is a heterogeneous disease with genetic and biochemical dysregulation background. The dysregulation happens in a few important signalling pathways, including Ras signalling, p53 signalling and Wnt/β-catenin signalling. This will lead to the malignant transformation of a normal cell to a cancer cell. Cancer cells are mainly caused by the alterations of multiple tumour suppressor genes and oncogenes. Research analysis was conducted to identify a better survival rate and prognosis outcome on colorectal tumours, especially in this study where the expression of tumour protein 53 (TP53) and B-cell lymphoma 2 (Bcl-2) biomarkers via immunohistochemical staining were targeted.